Chinas Greater Bay Area; China's Greater Bay Area - Britta Kuhn (Wirtschaftsdienst, 2021)
Die Volksrepublik China will wichtige Städte ihrer südöstlichen Küstenprovinz Guangdong eng mit Hongkong und Macao verbinden. Geplant ist ein integrierter Wirtschaftsraum, der bis spätestens 2035 eine globale Führungsrolle einnehmen soll. Die Grundidee ist nicht neu, nimmt aber zunehmend Gestalt an. Es gibt allerdings auch große Hindernisse. – – Economic cooperation among mainland China, Hong Kong and Macao has deepened quickly since 2019. A roadmap for China's southeastern province Guangdong promotes a common development of nine municipalities within the Pearl River Delta and the two Special Administrative Regions. The Chinese government wants this combined Greater Bay Area to become a highly innovative city cluster with world-class technologies and industries. Fully integrated transport networks and many pilot schemes are on their way. They will probably end the 'one country, two systems'-principle much before schedule. However, the ambitious plan faces impediments such as political tensions, trade confl icts and the COVID-19 pandemic.
Keywords: F15; F21; O53; 330; Wirtschaftsraum; Ballungsraum; Guangdong; China